INFLUENCE OF ROLE EFFICACY ON EMPLOYEE COMMITMENT - M. Sivapriya,; A. Govindarajan,; Ilankadhir M, (International Journal of Psychosocial Rehabilitation, 2020)
Role efficacy is widely accepted as a motivational tool for predicting optimistic job-related behaviours, association between role efficacy and organisational commitment has not been tested empirically in detail. This research was aimed at examining the previously underexplored relationship between role effectiveness and organisational commitment within the context of the Indian pharmaceutical industry. The findings of the quantitative analysis methodology used showed that the position effectiveness could contribute successfully to the organisational engagement under review. The key points to note, though, are that it is important to accept the views of the role incumbent on role creation.,